2015
DOI: 10.1080/15685551.2015.1012622
|View full text |Cite
|
Sign up to set email alerts
|

Novel pH sensitive composite hydrogel based on functionalized chitosan/clay for the controlled release of a calcium channel blocker

Abstract: The concept of novel drug delivery systems aims at achieving systematically improved therapeutic success for drugs including those that have limited use because of toxicity, uneven distribution pattern, stability and formulation of difficulties. The paper reveals the potential uses of novel hybrids of oleic acid-g-chitosan and montmorillonite (OA-g-CS/MMT) in controlled drug delivery applications. A calcium channel blocker is a chemical that disrupts the movement of calcium (Ca 2+ ) through calcium channels. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 42 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…As reported, the Ca 2+ cross-linked SA film would greatly enhance the mechanical performance. Besides, when introducing MMT, the geometry of SiO 4 tetrahedrons on the surface of the aluminosilicates contributes to form hydrogen bonds (the Velcro effect), which further improves the interfacial interactions with the CSA by numerous hydrogen bond interaction networks. , Therefore, it remains as a powerful interface interaction within the layers in the CSA-M0.6 film. As for the CSA-M0.6-T20mg sandwich film, the sandwich structure is obvious to observe.…”
Section: Resultsmentioning
confidence: 99%
“…As reported, the Ca 2+ cross-linked SA film would greatly enhance the mechanical performance. Besides, when introducing MMT, the geometry of SiO 4 tetrahedrons on the surface of the aluminosilicates contributes to form hydrogen bonds (the Velcro effect), which further improves the interfacial interactions with the CSA by numerous hydrogen bond interaction networks. , Therefore, it remains as a powerful interface interaction within the layers in the CSA-M0.6 film. As for the CSA-M0.6-T20mg sandwich film, the sandwich structure is obvious to observe.…”
Section: Resultsmentioning
confidence: 99%
“…(Table 2) presents the main articles and their peculiarities in the different systems (clay AND drug) used for the purpose of incorporating and releasing the drug in the human organism. Among the evaluated drugs, the classes are: analgesics [4], anticancer [16][17][18] antibiotics, anti-inflammatories [19,20] antibacterials [20][21][22] and vitamins [23][24][25]. The clays, natural or synthetic, that stand out in these studies are: montmorillonite, halloysite, laponite, palygorskite and magnesium phyllosilicates.…”
Section: Published Articlesmentioning
confidence: 99%
“…For the authors [4,20,46] all results suggest that it is possible to prepare nanocomposites in which their properties can be controlled by the clay content present in the nanocomposite. Nu-merous studies are reported in the literature regarding the kinetic release study profile [18][19][20][59][60][61]. In the studies ofthe kinetics of in vitro release of 10-hydroxycamptotcin from the nanocomposites were adjusted to the kinetic model of pseudo-second order.…”
Section: Articles Researchmentioning
confidence: 99%
“…25 CT is the second most abundant nontoxic cationic polysaccharide, composed of b-(1,4)22-amino-2-deoxy-D-glucose and is widely used in the biomedical field because of its excellent physiochemical properties and its biocompatibility and biodegradability in an aqueous environment. [26][27][28][29] Our research group has already reported the use of a thiolated chitosan/poly(lactic acid) blend incorporated in methionine-modified montmorillonite for the controlled release of amoxicillin (AMO) in the intestinal pH. 30 The hydrophilic nature and higher solubility of CT in an acidic medium prevents its ability to control the release of drug molecules.…”
Section: Introductionmentioning
confidence: 99%